THE MEANING OF ONE DIRECTION’S SONG’S IN “MIDNIGHT MEMORIES ALBUM” - Amalia, Qhusnul; Abdullah, Abdullah; Nasta, Mardiyanah (Faculty of Languages and Literature, Universitas Negeri Makassar, 2024)
This research discusses Meaning in the song of One Direction in the “Midnight Memories” album. It aims to analyze the meaning of the song based on the theory of Leech (1981) and Yule (1960) to analyze the types also to know how the implied meanings are presented in each song. This study used a qualitative descriptive research methodology. The results of this research show that there are 52 extracts describing the types of meaning found of the One Direction songs in